Masa Depan Hak Penyandang Disabilitas di Aceh: Sebuah Tinjauan Hak Asasi Manusia - Muhammad Arizka Wahyu; Jummadi Saputra; Putra Aguswandi (Yayasan Madinah Al-Aziziyah, 2026)
Persons with disabilities constitute a vulnerable group that continues to face various barriers in obtaining equal access to their fundamental rights, despite the fact that the protection of the rights of persons with disabilities has been guaranteed through various international, national, and regional legal instruments. In Aceh, problems such as limited accessibility to public facilities, inclusive education, healthcare services, employment opportunities, and participation in social and political life indicate that a gap remains between legal norms and their implementation in practice. This study aims to analyze the future fulfillment of the rights of persons with disabilities in Aceh from a human rights perspective by examining the development of the applicable legal framework, the current conditions of persons with disabilities, and the implementation of Aceh Qanun Number 2 of 2025 concerning the Fulfillment of the Rights of Persons with Disabilities. This study employs normative legal research using a statutory approach and a human rights approach. Data were obtained through a literature review of international legal instruments, national laws and regulations, Aceh Qanun, as well as relevant literature and supporting documents. The findings indicate that Aceh Qanun Number 2 of 2025 represents a progressive step toward strengthening the protection and fulfillment of the rights of persons with disabilities in Aceh, as it incorporates the principles of equality, non-discrimination, accessibility, and participation. Nevertheless, its effective implementation still faces several challenges, including budgetary constraints, weak inter-agency coordination, limited accessible facilities, and persistent social stigma against persons with disabilities. Therefore, stronger commitment from the regional government, society, and all relevant stakeholders is required to ensure that the qanun is implemented effectively and sustainably in order to realize an inclusive and equitable Aceh for persons with disabilities.